Transformation of AI-Enabled Collaborative Pedagogy in TEFL for Sport Education Students - Yohanes Gatot Sutapa Yuliana, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
TEFL Learning Methodology for No speaker original will experience Lots difficulties. Native speakers do not every moment can accompany in the learning process. Therefore that, help like AI becomes offer interesting as A choice in effort make it easier For study.Objectives. This For examine how AI plays a role in This TEFL Methodology learning.Materials and Methods. The techniques used is literature review with analysis using PRISMA. Keywords used "artificial intelligence" and "English language learning" were searched in WOS, and 69 articles were obtained. Next restricted only open access and obtained 30 articles. Results. This reviewed based on contents with read abstract and it turns out only 25 matching articles left with theme. Based on analysis conducted it turns out this AI has help good lecturer and student in Study teaches TEFL Methodology and has accepted by society academic. AI helps in understanding reading, vocabulary, grammar correction, writing correction, searching literature or in a way direct give bait back. Many things positive has achieved with learning utilization of AI based on studies literature confirmed. However thus there is also an issue negative about ethics, privacy and fear to dependence in long term that will turn off creativity.Conclusions. AI has capable of facilitate student in TEFL Methodology learning that targets skills, reading, writing, listening, and communicating. AI can push TEFL Methodology learning in transformative and adaptive especially those related to with approaches collaborative that prioritizes interaction dynamic in practice